Overkill : an Alex Hawke novel - Bell, Ted; OverDrive, Inc. (New York : William Morrow, 2018)
"Putting it all on the line to rescue his kidnapped son pits counterspy Alex Hawke against Russian President Vladimir Putin in this action-packed thriller from New York Times bestselling author Ted Bell. On a ski vacation in the Swiss Alps high above St. Moritz, Alex Hawke and his young son, Alexei, are thrust into danger when the tram carrying them to the top of the mountain bursts into flame, separating the two. Before he can reach Alexei, the boy is snatched from the burning cable car by unknown assailants in a helicopter. Meanwhile, high above the skies of France, Vladimir Putin is aboard his presidential jet after escaping a bloodless coup in the Kremlin. When two flight attendants collapse and slip into unconsciousness, the Russian leader realizes the danger isn't over. Killing the pilots, he grabs a parachute, steps out of the plane. and disappears. Hawke has led his share of dangerous assignments, but none with stakes this high. To save his son, he summons his trusted colleagues, Chief Inspector of Scotland Yard Ambrose Congreve, former U.S. Navy SEAL Stokley Jones, Jr., and recruits a crack Hostage Rescue Team--a group of elite soldiers of fortune known as "Thunder & Lighting." Before they can devise a rescue plan, Hawke must figure out who took his boy--and why. An operative who has fought antagonists around the globe, Hawke has made many enemies; one in particular may hold the key to finding Alexei before it's too late. But an unexpected threat complicates their mission. Making his way to "Falcon's Lair," the former Nazi complex created for Hitler, Putin is amassing an impressive armory that he intends to use for his triumphant return to Moscow. Only one man can smash the Russian president's plan for domination--a master counterspy who will cross every line to save his son. and maybe save the world itself in the bargain"--.
"Counterspy Alex Hawke goes all out to rescue his son and takes on Russian President Vladimir Putin in the bargain in the latest action-packed thriller in Ted Bell's New York Times bestselling series"--
Electronic book.
Electronic reproduction.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Hawke, Alex (Fictitious character) -- Fiction; Intelligence officers -- Fiction; Kidnapping -- Fiction; FICTION / Espionage; FICTION / Action & Adventure; Advantage title -- Fiction; Adventure fiction; Suspense fiction; Electronic books; Spy fiction